2010
DOI: 10.1021/jo1009239
|View full text |Cite
|
Sign up to set email alerts
|

Total Synthesis of Depsilairdin

Abstract: The total synthesis of depsilairdin, a host-selective phytotoxin isolated from Leptosphaeria maculans (the causal agent of blackleg disease of oilseed Brassicas), has been achieved by N-terminal extension of a suitably protected derivative of the hitherto unknown amino acid (2S,3S,4R)-3,4-dihydroxy-3-methyl-proline (Dhmp) followed by esterification with lairdinol A. The latter esterification, complicated by the sterically hindered nature of the carboxyl group, was accomplished by a novel method involving react… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 90 publications
0
3
0
Order By: Relevance
“…The structure of phomalide has been recently resolved as a rare cyclic depsipeptide with three a-amino acids and two a-hydroxy acids ( Fig. Analysis of phytotoxicities showed that the three analogs were no longer toxic to both brown mustard and canola, suggesting that the presence of Dhmp in the chemical structure of depsilairdin is required for its biological activity and host-selectivity to brown mustard (Ward & Pardeshi, 2010). Interestingly, the structural analog isophomalide that contains (Z)-dehydrobutyrine shows no phytotoxic activity against Brassica species, while the saturated dihydrophomalide causes chlorotic symptoms on the resistant brown mustard but not on canola, indicating that both the presence and configuration of the (E)-double bond is crucial for selective phytotoxicity (Siodlak et al, 2011).…”
Section: Sm Hsts Produced By Dothideomycetesmentioning
confidence: 99%
See 1 more Smart Citation
“…The structure of phomalide has been recently resolved as a rare cyclic depsipeptide with three a-amino acids and two a-hydroxy acids ( Fig. Analysis of phytotoxicities showed that the three analogs were no longer toxic to both brown mustard and canola, suggesting that the presence of Dhmp in the chemical structure of depsilairdin is required for its biological activity and host-selectivity to brown mustard (Ward & Pardeshi, 2010). Interestingly, the structural analog isophomalide that contains (Z)-dehydrobutyrine shows no phytotoxic activity against Brassica species, while the saturated dihydrophomalide causes chlorotic symptoms on the resistant brown mustard but not on canola, indicating that both the presence and configuration of the (E)-double bond is crucial for selective phytotoxicity (Siodlak et al, 2011).…”
Section: Sm Hsts Produced By Dothideomycetesmentioning
confidence: 99%
“…Recently, the complete synthesis of depsilairdin and three depsilairdin analogs, in which the Dhmp residue was replaced with L-proline and cis-and trans-4-hydroxy-L-proline has been achieved. Analysis of phytotoxicities showed that the three analogs were no longer toxic to both brown mustard and canola, suggesting that the presence of Dhmp in the chemical structure of depsilairdin is required for its biological activity and host-selectivity to brown mustard (Ward & Pardeshi, 2010). A new set of selective phytotoxins, named maculansins A and B have also been recently isolated from virulent isolates of L. maculans (Pedras & Chumala, 2011).…”
Section: Sm Hsts Produced By Dothideomycetesmentioning
confidence: 99%
“…265 Enantioselective total syntheses of dihydrojuneol 266 and (+)-carainterol A 267 have been accomplished, while depsilairdin has been synthesized by esterification of lairdinol A with a tetradepsipeptide. 268 A preparation of ar-occidol has been reported. 269 The sesquiterpene 1a-hydroxy-b-dihydroagarofuran has been obtained from the fruits of Cryptomeria fortunei.…”
Section: Germacranementioning
confidence: 99%